Embryogenic Callus as Target for Efficient Transformation of Cyclamen persicum Enabling Gene Function Studies - Ratjens, Svenja; Mortensen, Samuel; Kumpf, Antje; Bartsch, Melanie; Winkelmann, Traud (Frontiers in Plant Science, 2018)
Cyclamen persicum is an ornamental plant with economic relevance in many parts of the world. Moreover, it can be regarded as an applied model for somatic embryogenesis, since transcriptomic, proteomic, and metabolomic comparisons have revealed insights into this regeneration process on the molecular level. To enable gene function analyses, the aim of this study was to establish an efficient Agrobacterium tumefaciens-mediated genetic transformation protocol for C. persicum. For the first time, embryogenic callus cultures were used as a target material and. The advantages of embryogenic callus are the defined and known genotype compared to seedlings, the high regeneration potential and the stability of the regenerated plants. Embryogenic cells were precultured for ten days before being co-cultured with A. tumefaciens for two days. Selection of transgenic cells carrying the hygromycin phosphotransferase gene was achieved by increasing hygromycin concentrations, which were adjusted depending on the plant genotype. A. tumefaciens strains EHA105 and LBA4404 were most efficient for transformation, resulting in transformation efficiencies of up to 43% and 20%, respectively. However, the variation between experiments was pronounced. Plants were regenerated from transformed embryogenic callus after 24 weeks, and the presence of the transgenes was verified by PCR, Southern hybridization and a histochemical GUS assay. No residual bacteria were detected in the regenerated plants. The protocol was successfully applied to a second C. persicum genotype. Moreover, two reporter constructs, the auxin-responsive promoter DR5 driving the gus gene and the redox sensor roGFP2_Orp1, were transferred to C. persicum genotypes, allowing the localization of high auxin concentrations and reactive oxygen species in order to study their roles in somatic embryogenesis in the future.